2017
DOI: 10.1002/cncr.31072
|View full text |Cite
|
Sign up to set email alerts
|

NCCTG N0879 (Alliance): A randomized phase 2 cooperative group trial of carboplatin, paclitaxel, and bevacizumab ± everolimus for metastatic melanoma

Abstract: Both experimental arms demonstrated activity, with a PFS of >5 months. However, the addition of everolimus to CPB failed to improve outcomes, with increased toxicity noted. These findings replicate the moderate antitumor activity of CPB, with future development possibly in combination with targeted or immunotherapy. Cancer 2018;124:537-45. © 2017 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 30 publications
(49 reference statements)
0
29
0
Order By: Relevance
“… 4 6 For example, in a clinical Phase II randomized controlled trial, combining bevacizumab with carboplatin and paclitaxel chemotherapy medicine in the control group for treatment, the ORR was 13%, the median PFS was 5.6 months, and the median OS was 14.5 months, and when erolimus was added to the experimental group, the ORR could be increased to 23%, while the median PFS and the median OS were not as good as those in the control group. 6 The above research indicated that antiangiogenic inhibitors may be effective in MM treatment. Therefore, we used Apatinib Mesylate Tablet, a novel small-molecule inhibitor of VEGFR-2 tyrosine kinase, for treating the metastatic MM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 4 6 For example, in a clinical Phase II randomized controlled trial, combining bevacizumab with carboplatin and paclitaxel chemotherapy medicine in the control group for treatment, the ORR was 13%, the median PFS was 5.6 months, and the median OS was 14.5 months, and when erolimus was added to the experimental group, the ORR could be increased to 23%, while the median PFS and the median OS were not as good as those in the control group. 6 The above research indicated that antiangiogenic inhibitors may be effective in MM treatment. Therefore, we used Apatinib Mesylate Tablet, a novel small-molecule inhibitor of VEGFR-2 tyrosine kinase, for treating the metastatic MM.…”
Section: Discussionmentioning
confidence: 99%
“… 2 In the advanced MM, antiangiogenic therapy is still an important therapeutic method. Related studies using chemotherapy combined with recombinant human Endostar ™ (endostatin), 3 or monoclonal antibody drugs (McAb) of VEGFR, 4 6 have confirmed that chemotherapy combined with antiangiogenic therapy can improve the survival of patients with advanced MM. Therefore, in our study, apatinib mesylate tablet was used as the main drug to treat patients with Stage IV MM who failed conventional chemotherapy, in order to evaluate the clinical efficacy and safety of the drug.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, a recent study evaluated the combination of everolimus, bevacizumab, carboplatin and paclitaxel (CPB) in a randomized phase II trial. A total of 149 patients affected by stage IV melanoma were treated with CPB or with CPB plus everolimus: no differences in terms of PFS or OS were noted among the two groups, but everolimus strongly increased toxicity (McWilliams et al, 2018).…”
Section: Mtormentioning
confidence: 99%
“…A recent study evaluated the addition of everolimus to carboplatin, paclitaxel, and bevacizumab; this combination was found to be ineffective in metastatic melanoma because of inability to give the full dose of everolimus, predominantly because of cytopenias . Although it was a negative study, the investigators reported that the everolimus combination arm performed exceptionally well, receiving >30 cycles of therapy .…”
mentioning
confidence: 99%